1981
DOI: 10.1002/em.2860030108
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic activation of carcinogens in the salmonella mutagenicity assay by hamster and rat liver S‐9 preparations

Abstract: Before exerting a carcinogenic o r mutagenic effect, many carcinogens must undergo metabolic activation. Liver S-9 preparations from rats treated with Aroclor 1 2 5 4 (AC) have been widely used to extend the ability of the Salmonella mutagenicity assay t o detect such nondirect-acting agents. We compared the mutagen-activating capabilities of liver S-9 preparations f r o m both Syrian golden hamsters and Sprague-Dawley rats. T h e comparison was made between S-9 fractions from untreated, and phenobarbital (PB)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0
1

Year Published

1982
1982
1990
1990

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 21 publications
3
7
0
1
Order By: Relevance
“…These results are consistent with the data of Raineri et al (1981) that hamster liver S-9 provides more effective metabolism of 3-methylcholanthrene, and with our experimental evidence that the increased metabolic capacity of the activation mixture is crucial to enhanced mutagenesis.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with the data of Raineri et al (1981) that hamster liver S-9 provides more effective metabolism of 3-methylcholanthrene, and with our experimental evidence that the increased metabolic capacity of the activation mixture is crucial to enhanced mutagenesis.…”
Section: Discussionsupporting
confidence: 93%
“…Mutagenesis assays were performed as described (24,25), with each assay mixture containing 3 mg of total lysate protein from vacciniainfected cells. To analyze aflatoxin B1 binding to DNA, =6 x 106 cells were infected with recombinant vaccinia virus and [3H]aflatoxin B1 (15 Ci/mmol, Moravek Biochemicals, San Francisco, CA; 1 Ci = 37 GBq) was added to 13 ml of culture medium in a 10-cm-diameter dish.…”
Section: Ivb1mentioning
confidence: 99%
“…The superiority of hamster S-9 for the activation of complex PAH mixtures was suggested by several studies (Raineri et al, 1981;Amacher and Turner, 1980;Oberly et al, 1982). Raineri et al (1981) showed that induced hamster S-9 is superior for activation of 3-methyl-cholanthrene, but somewhat less effective than the rat preparation for B[a]P, while Oberly et al (1982) showed approximately equal mutagenicity of 3-methylcholanthrene and dimethylbenzanthracene in the mouse lymphoma assay using rat, mouse, or hamster S-9. However, in the latter study, considerably less toxicity was induced at a given concentration with the hamster preparation.…”
Section: Discussionmentioning
confidence: 89%
“…Instead of the standard Aroclor 1254-induced rat liver S-9, a corresponding preparation from Syrian golden hamsters is used, and the level of the required cofactor, NADP, has been increased from 4 to 8 mM. The superiority of hamster S-9 for the activation of complex PAH mixtures was suggested by several studies (Raineri et al, 1981;Amacher and Turner, 1980;Oberly et al, 1982). Raineri et al (1981) showed that induced hamster S-9 is superior for activation of 3-methyl-cholanthrene, but somewhat less effective than the rat preparation for B[a]P, while Oberly et al (1982) showed approximately equal mutagenicity of 3-methylcholanthrene and dimethylbenzanthracene in the mouse lymphoma assay using rat, mouse, or hamster S-9.…”
Section: Discussionmentioning
confidence: 99%